Photoelectrochemical Properties of Porous Si/TiO2 Nanowire Heterojunction Structure. (1st July 2020) - Wang, Ji; Yang, Jikai; Zhao, Yiming; Wang, Guozheng
Abstract : The porous silicon as substrate material was prepared by metal-assisted chemical etching (MACE) method. The TiO2 nanowire cover layer on porous silicon was prepared by hydrothermal method. Thus, porous Si/TiO2 nanowire heterostructure was obtained. The formation of the porous Si/TiO2 nanowire heterostructure was confirmed by X-ray diffraction (XRD) and scanning electron microscope (SEM). The results of diffuse reflection spectra (DRS) show that porous Si/TiO2 nanowire has the highest antireflectivity among the four tested samples. Photoelectric catalysis (PEC) and photocurrent measurement show that the porous Si/TiO2 nanowire heterostructure has higher photoelectric catalytic and photocurrent activity than the other samples under the simulated solar light and visible light irradiation. The results showed that the construction of the porous Si/TiO2 nanowire heterostructure improved the photoelectrochemical properties, which is attributed to the heterogeneous effect and window effect.